Antituberculosis agent diaportheone B: synthesis, absolute configuration assignment, and anti-TB activity of its analogues - Swaroop, Pandrangi Siva; Raut, Gajanan N.; Gonnade, Rajesh G.; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2012)
First synthesis of diaportheone B, an antituberculosis agent isolated from endophytic fungus Diaporthe sp. P133 is reported using two complementary routes, a one step and a three-step sequence. The absolute configuration of diaportheone B was determined by using X-ray crystal structure analysis of its dibromo derivative. In addition, we have prepared several close analogues of diaportheone B and determined their anti-TB potential using Alamar-blue assay (H(37)Rv).

Synthesis of isomeric corniculatolides - Raut, Gajanan N.; Chakraborty, Kasturi; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Tetrahedron Letters, 2012)
Synthesis of three natural macrolides 11-O-methylcorniculatolide A, 11-O-methylisocorniculatolide A and isocorniculatolide A is reported using a simple, straight forward and high-yielding route. The present synthesis confirms the assigned molecular structures and provides an access to sufficient quantities of the natural products for the biological evaluation. In addition, we have determined the anti-TB potential of the three natural compounds using Alamar-Blue assay (H(37)Rv) and found no significant inhibitory activity at 100 mu g/ml. Excellent yields, short sequence and useful SAR information are the highlights of the present work. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Diaryl ether; Isocorniculatolide; Macrocyclization; Mitsunobu reaction; Total synthesis

Differential rubisco content and photosynthetic efficiency of rol gene integrated Vinca minor transgenic plant: correlating factors associated with morpho-anatomical changes, gene expression and alkaloid productivity - Verma, Priyanka; Khan, Shamshad Ahmad; Masood, Nusrat; Manika, N.; Sharma, Abhishek; Verma, Neha; Luqman, Suaib; Mathur, Ajay K. (Journal of Plant Physiology, 2017)
Transgenic plants obtained from a hairy root line (PVG) of Vinca minor were characterized in relation to terpenoid indole alkaloids (TIAs) pathway gene expression and vincamine production. The hairy roots formed callus with green nodular protuberances when transferred onto agar-gelled MS medium containing 3.0 mg/l zeatin. These meristematic zones developed into shoot buds on medium with 1.0 mg/l 2, 4-dichlorophenoxyacetic acid and 40 mg/l ascorbic acid. These shoot buds subsequently formed rooted plants when shifted onto a hormone-free MS medium with 6% sucrose. Transgenic nature of the plants was confirmed by the presence of rol genes of the Ri plasmid in them. The transgenic plants (TP) had elongated internodes and a highly proliferating root system. During glass house cultivation TP consistently exhibited slower growth rate, low chlorophyll content (1.02 +/- 0.08 mg/gm fr. wt.), reduced carbon exchange rate (2.67 +/- 0.16 mu mol m(-2) s(-1)), less transpiration rate (2.30 +/- 0.20 mmol m(-2) s(-1)) and poor stomatal conductance (2.21 +/- 0.04 mmol m-2 s(-1)) when compared with non-transgenic population. The activity of rubisco enzyme in the leaves of TP was nearly two folds less in comparison to non-transgenic controls (1.80 milliunits ml(-1) mg protein-1 against 3.61 milliunits ml(-1) mg protein-1, respectively). Anatomically, the TP had a distinct tetarch arrangement of vascular bundles in their stem and roots against a typical ployarched pattern in the non-transgenic plants. Significantly, the transgenic plants accumulated 35% higher amount of total TIAs (3.10 +/- 0.21% dry wt.) along with a 0.03% dry wt. content of its vasodilatory and nootropic alkaloid vincamine in their leaves. Higher productivity of alkaloids in TP was corroborated with more than four (RQ = 4.60 +/- 0.30) and five (RQ = 5.20 +/- 0.70) times over-expression of TIAs pathway genes tryptophan decarboxylase (TDC) and strictosidine synthase (STR) that are responsible for pushing the metabolic flux towards TIAs synthesis in this medicinal herb.

Pyrethrin accumulation in elicited hairy root cultures of chrysanthemum cinerariaefolium - Khan, Shamshad A.; Verma, Priyanka; Banerjee, Suchitra; Chaterjee, Arnab; Tandon, Sudeep; Kalra, Alok; Khaliq, Abdul; Rahman, Laiq Ur (Plant Growth Regulation, 2017)
The flowers of Pyrethrum (Chrysanthemum cinerariaefolium) are known to contain Pyrethrins that are naturally occurring potential insecticide. Hairy roots were induced from leaves of C. cinerariaefolium using Agrobacterium rhizogenes strain A4. The root clones were characterized in to four groups i.e. thick, unbranched (D2 and D5), thin, highly branched (D3), thick, branched (B2) and thick, highly branched (D1, D6). Six established hairy root clones showed the presence of pyrethrin and were selected for elicitation studies. Growth kinetics studies revealed highest growth index in hairy root clone D1 (592.0) followed by D6 and D3 on dry weight basis after 40 days of culture. The maximum pyrethrin content was found in the clone D3 (7.2 mg/g dw) which is comparable to the flowers obtained from the variety "Avadh". Hairy root clone D2 (5.2 mg/g dw) and D6 (1.3 mg/g dw) contained pyrethrin but in less amount as compared to clone D3. The PCR analysis showed the presence of rol B and rol C genes in all the six hairy root clones while rol A was detected only in D2 clone. The methanolic extract of D3 clone showed antifungal activities against phytopathogenic fungal strains which were found maximum against Curvuleria andropogonis followed by Colletotrichum acutatum and Rhizoctonia solani. Hairy root clones D2, D3 and D6 were elicited with culture filtrate of endophytic fungus (Fusarium oxysporum) and bacteria (Bacillus subtilis). The culture filtrate (4.0 %v/v) of both the fungal and bacterial origin was found to be effective in enhancing the pyrethrin content in all the tested hairy root clones. Clone D3 showed maximum pyrethrin content on elicitation with F. oxysporum (9.7 mg/g dw) and B. subtilis (9.7 mg/g dw) culture filtrate, which is 32 % higher than the non elicited D3 hairy roots (7.2 mg/g dw). F. oxysporum also enhanced the hairy root growth resulting into the higher biomass yield of D3 (50 %) and D2 (76 %) in comparison to control non elicited hairy root clones of D3 and D2, respectively leading to higher pyrethrin yield.

Development of enhanced hypericin yielding transgenic plants and somaclones: high throughput direct organogenesis from leaf and callus explants of Hypericum perforatum - Khan, Shamshad A.; Verma, Priyanka; Arbat, Akshata; Gaikwad, Sushma; Parasharami, Varsha A. (Industrial Crops and Products, 2018)
Hypericum perforatum is well known for its anti-depressent properties due to the presence of hypericins and hyperforins. The direct regeneration protocol from leaf explants and Agrobacterium tumefaciens mediated genetic transformation is a prerequisite for gene transfer studies in this valuable plant system as H. perforatum has shown its recalcitrance to these studies previously. The aim of generating transgenic shoots or somaclones in the present study is to select high hypericine yielding H. perforatum plants. High throughput direct bud organogenesis from leaf explants has been achieved for the first time in this plant system on media combination of MS + 5.0 mg/l BAP + 1.0 mg/l. This medium interestingly also worked as the indirect regeneration media for generation of somaclones from callus cultures. Thus far optimized single media can be used for direct and indirect regeneration in H. perforatum. The direct regeneration frequency of plantlets from leaf explants was found to be 80% while 100% was the regeneration frequency noted for indirect plantlet regeneration from callus cultures. The optimized direct regeneration protocol from leaf explants was utilized for A. tumefaciens (harbouring pCAMBIA 1301) mediated genetic transformation studies with the aim of establishing transgenic lines of H. perforatum. The resultant study successfully gave rise to kanamycin resistant GUS positive shoots with transformation efficiency of 3136 +/- 3.6. A total of four transgenic H. perforatum clones namely T2, T3, T5 and T8 with different growth parameters were established, where highest of fivefold increase in hypericin content was recorded by T5 (276.8 +/- 9.2 mu g/g dry wt.) in comparison to control non transformed plants (35.6 +/- 2.7 mu g/g dry wt.). Interestingly the presence of serotonin and melatonin was also detected in transgenic plants on TLC basis. The transgenic nature of the plants was confirmed by PCR with amplification of uidA gene. Apart from it, from indirect regeneration from callus, total of ten somaclones were generated. The ISSR profiling of somaclones scored a total of 156 bands, among which 118 were polymorphic in nature. The glasshouse established soma clones showed up to twofold increase in hypericin content on HPLC analysis.
Keywords: Direct regeneration; Hypericin; Hypericum perforation; Indirect regeneration; ISSR; Somaclones; Transgenic plants

Overexpression of tryptophan decarboxylase and strictosidine synthase enhanced terpenoid indole alkaloid pathway activity and antineoplastic vinblastine biosynthesis in Catharanthus roseus - Sharma, Abhishek; Verma, Priyanka; Mathur, Archana; Mathur, Ajay (Protoplasma, 2018)
Terpenoid indole alkaloid (TIA) biosynthetic pathway of Catharanthus roseus possesses the major attention in current metabolic engineering efforts being the sole source of highly expensive antineoplastic molecules vinblastine and vincristine. The entire TIA pathway is fairly known at biochemical and genetic levels except the pathway steps leading to biosynthesis of catharanthine and tabersonine. To increase the in-planta yield of these antineoplastic metabolites for the pharmaceutical and drug industry, extensive plant tissue culture-based studies were performed to provide alternative production systems. However, the strict spatiotemporal developmental regulation of TIA biosynthesis has restricted the utility of these cultures for large-scale production. Therefore, the present study was performed to enhance the metabolic flux of TIA pathway towards the biosynthesis of vinblastine by overexpressing two upstream TIA pathway genes, tryptophan decarboxylase (CrTDC) and strictosidine synthase (CrSTR), at whole plant levels in C. roseus. Whole plant transgenic of C. roseus was developed using Agrobacterium tumefaciens LBA1119 strain having CrTDC and CrSTR gene cassette. Developed transgenic lines demonstrated up to twofold enhanced total alkaloid production with maximum ninefold increase in vindoline and catharanthine, and fivefold increased vinblastine production. These lines recorded a maximum of 38-fold and 65-fold enhanced transcript levels of CrTDC and CrSTR genes, respectively.

TIAs pathway genes and associated miRNA identification in Vinca minor: supporting aspidosperma and eburnamine alkaloids linkage via transcriptomic analysis - Verma, Priyanka; Singh, Noopur; Khan, Shamshad Ahmad; Mathur, Ajay Kumar; Sharma, Ashok; Jamal, Farrukh (Physiology and Molecular Biology of Plants, 2020)
V. minorcontains monomeric eburnamine-type of indole alkaloids having utilization as a neuro-medicinal plant. The biosynthetic pathway studies using miRNAs has been the focal point for plant genomic research in recent years and this technique is utilized to get an insight into a possible pathway level study inV. minoras understanding of genes in this prized medicinal plant is meagrely understood. The de novo transcriptomic analysis using Illumina Next gen sequencing has been performed in glasshouse shifted plant and transformed roots to elucidate the possible non confirmed steps of terpenoid indole alkaloids (TIAs) pathway inV. minor. A putative TIA pathway is elucidated in the study including twelve possible TIAs biosynthetic genes. The specific miRNA associated with TIAs pathway were identified and their roles were discussed for the first time inV. minor. The comparative analysis of transcriptomic data of glasshouse shifted plant and transformed roots showed that the raw reads of transformed roots were higher (83,740,316) compared to glasshouse shifted plant (67,733,538). The EST-SSR prediction showed the maximum common repeats among glasshouse shifted plant and transformed roots, although small variation was found in trinucleotide repeats restricted to glasshouse shifted plant. The study reveals overall 37 miRNAs which were observed to be true and can have a role in pathway as they can regulate the growth and alkaloid production. The identification of putative pathway genes plays an important role in establishing linkage between Aspidosperma and Eburnamine alkaloids.
Keywords: de novo transcriptomic analysis; EST-SSR; miRNA; Terpenoid indole alkaloids; Vinca minor

Development of enhanced hypericin yielding transgenic plants and somaclones: high throughput direct organogenesis from leaf and callus explants of Hypericum perforatum (Retraction of Vol 111, Pg 544, 2018) - Khan, A. Shamshad; Verma, Priyanka; Arbat, Akshata; Gaikwad, Sushma; Parasharami, A. Varsha (Industrial Crops and Products, 2021)

ZCTs knockdown using antisense LNA GapmeR in specialized photomixotrophic cell suspensions of Catharanthus roseus: Rerouting the flux towards mono and dimeric indole alkaloids - Verma, Priyanka; Khan, Shamshad Ahmad; Parasharami, Varsha; Mathur, Ajay Kumar (Physiology and Molecular Biology of Plants, 2021)
The present study was carried out to silence the transcription factor genes ZCT1, ZCT2 and ZCT3 via lipofectamine based antisense LNA GapmeRs transfection into the protoplasts of established photomixotrophic cell suspensions. The photomixotrophic cell suspensions with a threshold of 0.5% sucrose were raised and established using two-tiered CO2 providing flasks kept under high light intensity. The photomixotrophic cell suspensions showed morphologically different thick-walled cells under scanning electron microscopic analysis in comparison to the simple thin-walled parenchymatous control cell suspensions. The LC-MS analysis registered the vindoline production (0.0004 +/- 0.0001 mg/g dry wt.) in photomixotrophic cell suspensions which was found to be absent in control cell suspensions. The protoplasts were isolated from the photomixotrophic cell suspensions and subjected to antisense LNA GapmeRs silencing. Three lines, viz. Z1A, Z2C and Z3G were obtained where complete silencing of ZCT1, ZCT2 and ZCT3 genes, respectively, was observed. The Z3G line was found to show maximum production of vindoline (0.038 +/- 0.001 mg/g dry wt.), catharanthine (0.165 +/- 0.008 mg/g dry wt.) and vinblastine (0.0036 +/- 0.0003 mg/g dry wt.). This was supported by the multifold increment in the gene expression of TDC, SLS, STR, SGD, d4h, dat, CrT16H and Crprx. The present work indicates the master regulation of ZCT3 knockdown among all three ZCTs transcription factors in C. roseus to enhance the terpenoid indole alkaloids production. The successful silencing of transcription repressor genes has been achieved in C. roseus plant system by using photomixotrophic cell cultures through GapmeR based silencing. The present study is a step towards metabolic engineering of the TIAs pathway using protoplast transformation in C. roseus.
Keywords: Catharanthine; LC-MS; Protoplast; TIAs; Vinblastine; Vindoline

Homo and heterologous expression of the HpPKS2 gene in Hypericum perforatum and Bacopa monnieri - Khan, Shamshad Ahmad; Verma, Priyanka; Parasharami, Varsha A. (Plant Cell Tissue and Organ Culture, 2022)
Hypericum perforatum has been known to produce hypericin and hyperforin that are used in treating mild to moderate depression. The HpPKS2 (H. perforatum polyketide synthase 2) gene is assumed to play a role in hypericin biosynthesis. The HpPKS2 gene was overexpressed in homologous H. perforatum in vitro grown plants through Agrobacterium tumefaciens-mediated genetic transformations. It leads to the establishment of seven glass house acclimatized transgenic lines. Among them, the HP12 transgenic plant showed 9.8 fold enhancement in hypericin content (379.4 +/- 10.3 mu g/g dry wt) followed by 3-fold in HP41 (117.1 +/- 4.5 mu g/g dry wt) as compared to control plants. This was further supported by the real-time PCR studies where it registered up to 5 fold enhancement of HpPKS2 gene expression. On the other hand, the heterologous expression of the HpPKS2 gene in Bacopa monnieri resulted in the establishment of five transgenic plant clones that were successfully acclimatized under glasshouse conditions. Among them, BT4 was found to be very slow-growing. The BT3 line showed maximum expression of the HpPKS2 gene which surprisingly also upregulates the expression of the other metabolic pathway genes of B. monierri namely isopentyl- diphosphate delta isomerase (IDDI), squaline synthase (SQS) and acetyl CoA C acetyltransferase (AA). The HPLC analysis in the heterologous system revealed the maximum production of bacopaside I (9.86 +/- 1.0 mg/g dry wt), bacopaside II (5.89 +/- 0.9 mg/g dry wt) and bacopasaponin C (3.59 +/- 0.3 mg/g dry wt) by transgenic lines BT8, BT3 and BT4, respectively. This enhancement in bacopaside I, bacopaside II and bacopasaponin C production was more than 26-fold, 5-fold and 21-fold, respectively in comparison to the control non transformed plants. Key message Overexpression of the HpPKS2 gene in H. perforatum led to higher hypericin content in the native system while its expression in the heterologous system i.e. B. monnieri also improves bacopaside I, bacopaside II and bacopasaponin C production.
Keywords: Agrobacterium tumefacience; Bacopa monnieri; Bacopasides; Heterologous expression; HpPKS2; Hypericin; Hypericum perforatum; Transgenics